Sustainable Places 2019 2019
DOI: 10.3390/proceedings2019020001
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Energy Renovation Solution for Zero Energy Buildings and Neighbourhoods—The Experience of the RenoZEB Project

Abstract: Buildings are the key factor to transform cities and to contribute to recent European energy efficiency objectives for 2030 and long-term 2050. New buildings account to only 1–2% annually. Yet, ninety percent of the existing building stock in Europe was built before 1990, it is therefore necessary to promote their energy renovation to achieve the set objectives. Renovation solutions are available on the market, yet a wrong implementation and integration due to a lack of knowledge neither maximizes the energy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Due to the reduction of energy use during the lifetime of buildings, renovation resulted in a reduction of global warming potential [4]. Case studies have shown the viability of the nZEB renovation measures to improve the condition of residential building stock in Croatia [5], Spain [6,7], Poland [8], and the Mediterranean climate [9]. The outcomes show huge potential energy and economic savings and support deep energy renovation needs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the reduction of energy use during the lifetime of buildings, renovation resulted in a reduction of global warming potential [4]. Case studies have shown the viability of the nZEB renovation measures to improve the condition of residential building stock in Croatia [5], Spain [6,7], Poland [8], and the Mediterranean climate [9]. The outcomes show huge potential energy and economic savings and support deep energy renovation needs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is not assessed in all the projects, only in 13 of 18 projects. Indoor thermal conditions are assessed all these 13 projects (ENERPAT [9], EFFESUS [9], ALDREN [10], REFURB [13], RenoZEB [14], REVALUE [15], GrowSmarter [20], RemoUrban [21], STEEP [23], OptEEmAL [25], EASEE [26], Paradis [28] and Plan Zero CO2 [31]). In the case of GrowSmarter [20] standardized evaluation is applied by ISO-7730 [47] and ISO-7726 [48] International Standards.…”
Section: Assessment Methodologymentioning
confidence: 99%
“…With a different working field, the REFURB [12] [13] project proposes different renovation packages based not only on energy, also on features and needs of the dwelling and dwellers, creating a methodology. Furthermore, BIM (Building Information Modelling) based methodologies are also developed, like RenoZEB project [14], researching in new renovation constructive solutions using prefabricated elements. Another type of project is the development of an Energetic Action Plan for cities, the projects REPICATE [18], [19], GrowSmarter [20], ReemoUrban [35], and STEEP [22], [23]; they follow a similar schedule with three main working areas one of them being the improvement of energy efficiency of existing buildings.…”
Section: Characterisationmentioning
confidence: 99%
“…In the context of deep renovation, recent research suggests that the lack of properly trained energy efficiency professionals and construction workers, locally and in general, in the proper selection and installation of new constructional technologies is a significant barrier to adoption, both directly and indirectly [9][10][11]30]. For public sector organisations, procurement policies that favour price over quality can have a negative impact on deep renovation [43].…”
Section: Organisational Barriers To Deep Renovation Adoption and Usementioning
confidence: 99%
“…The key action for energy efficiency in buildings is reducing the demand for heating and cooling via renovation of the building envelope, using new low-energy-consuming equipment in general (and specifically, using more energy-efficient heating equipment), increasing the uptake and use of renewable solutions, as well as the adoption of "smart buildings" [6]. Recent research suggests that renovation efforts are adversely impacted across the value chain by a number of human, organisational, technological and market factors [8][9][10][11]. To address these issues, a combination of the greater use of ICTs in construction, renovation and maintenance and novel solutions for incentivising and financing renovation, promoting and driving demand for renovation and transforming the construction sector is needed [7].…”
Section: Introductionmentioning
confidence: 99%